The Role of Islamic Boarding Schools (Pesantren) in Community Social Life - Anisa Rosalia; Umuy Muzayanah; Hapipi Hapipi (International Research and Development for Human Beings (IRDH), 2024)
Islamic boarding schools or Pesantren have an important role in character formation in Indonesia. Islamic boarding schools also contribute to nation and state development through community service in the fields of religion and education. This research was written using a literature review. The results of this research reveal that Islamic boarding schools have a role in strengthening Islamic institutional capacity and strengthening Indonesian Islamic traditions in Indonesia. Friendly Islam by respecting local culture, carrying out cultural acculturation and mingling with local communities and respecting differences are among the teachings of the walisongo and ulama that we should be able to maintain.